Characterisation of polylactic acid biocomposites made from prepregs composed of woven polylactic acid/hemp–Lyocell hybrid yarn fabrics. (February 2016) - Baghaei, Behnaz; Skrifvars, Mikael
Abstract: This paper describes the mechanical properties and water absorption characteristics for biocomposites made from woven PLA/hemp/Lyocell prepregs. The aim was to improve the properties with the addition of Lyocell fibre into a hybrid yarn. Well-aligned hybrid yarns composed of hemp/PLA, hemp–Lyocell/PLA, respective, Lyocell/PLA were made by wrap spinning. Unidirectional satin fabrics were made by weaving with PLA (warp) and the hybrid yarns (weft). Uniaxial composites were fabricated with 30 fibre mass% using compression moulding. The composites were investigated for tensile, flexural and impact properties. Combining hemp with Lyocell in a PLA matrix improves the mechanical properties, compared to hemp/PLA composites. The composite made from the satin Lyocell/PLA fabric gave the best mechanical properties. The type of fibre reinforcement compositions did not significantly affect the water absorption of the biocomposites. Scanning electron microscopy showed that fibre pull-outs appear more often in hemp/PLA composites than in composites also including Lyocell fibre.